2003
DOI: 10.1139/t03-052
|View full text |Cite
|
Sign up to set email alerts
|

Performance of instrumented large-scale unreinforced and reinforced embankments loaded by a strip footing to failure

Abstract: The paper describes an experimental investigation in which two large-scale geosynthetic reinforced soil embankments and one unreinforced soil embankment were taken to collapse under a strip footing placed close to the crest. One reinforced embankment was constructed with a relatively extensible and weak polypropylene geogrid and the second with a relatively strong and stiff high-density polyethylene geogrid. The geometry of the unfaced embankments, sand soil, and loading arrangement were the same for all three… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(27 citation statements)
references
References 9 publications
1
24
0
2
Order By: Relevance
“…The results obtained by using bicycle gear cables could only be considered qualitatively throughout the analysis. Bathurst et al (2003) employed the high-elongation strain gauge for strain measurement of the geogrid, and found that the relationship between the local strain and the global strain of the geogrid was nonlinear over several grid apertures. Flexible displacement sensors were employed to measure the strain of the geogrid being transformed into the tensile force by using the stiffness of the geogrid (Chen et al, 2009a;Yang et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…The results obtained by using bicycle gear cables could only be considered qualitatively throughout the analysis. Bathurst et al (2003) employed the high-elongation strain gauge for strain measurement of the geogrid, and found that the relationship between the local strain and the global strain of the geogrid was nonlinear over several grid apertures. Flexible displacement sensors were employed to measure the strain of the geogrid being transformed into the tensile force by using the stiffness of the geogrid (Chen et al, 2009a;Yang et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…For example, laboratory model tests on the behaviour of a model footing on flat ground under vertical cyclic loading have been reported by several researchers (Das and Shin 1994;Das and Shin 1996;El Sawwaf and Nazir 2010;Puri et al 1993;Raymond and Komos 1978;Yeo et al 1993). On the other hand, slope stability under monotonic foundation loading has also been investigated by many researchers (Alamshahi and Hataf 2009;Bathurst et al 2003;Lee and Manjunath 2000;Selvadurai and Gnanendran 1989;Shields et al 1977;Shin and Das 1998;Yoo 2001). However, studies on the behaviour of a foundation near sloped fill under cyclic loading is hard to find in the literature until recently when Islam and Gnanendran (2012) and El Sawwaf and Nazir (2012) performed few physical model study.…”
Section: Figure 1 Foundation Of a Bridge Abutment Near Sloped Fillmentioning
confidence: 99%
“…Choudhary et al (2010) suggested that the embedment ratio (z/B) for reinforced slope (N = 1-7) should be chosen from 0.25 to 3.0 depending on number of geogrid layers. Bathurst et al (2003) reported the reinforcement spacing as 0.75m (N=4) for large scale scale test. Based on the above reports the embedment ratio (z/B) for reinforced slope (N = 1-4) were chosen from 0.25 to 1.0 in the present investigation.…”
Section: Fig 5 Schematic Test Arrangementmentioning
confidence: 99%